Evaluation of Some Immunological and DNA Damage Parameters among Patients with Rheumatoid Arthritis - Salman, Shams A.; AL-Jumaily, Rakad M. Kh (Iraqi Journal of Science, 2024)
Rheumatoid arthritis (RA) can cause permanent joint damage and disability through inflammation in the joints. Other organs, such as blood vessels, lungs, heart, eyes and skin may also get affected. This study aimed to evaluate the changes of some oxidative stress markers including oxidative DNA damage and the clinical outcomes that are associated with Iraqi rheumatoid arthritis patients. Commercial enzyme linked immunosorbent assay (ELISA) kits were applied to evaluate malondialdehyde (MDA), DNA damage marker 8-hydroxy-2-deoxyguanosine (8-OHDG), and glutathione peroxidase 3 (GPX3) levels in serum of 60 patients having RA with ages ranging between 20-70 years and 30 age-matched healthy controls. The results showed a significant increase in MDA levels in RA patients compared with the control group. Also, the levels of GPX3 decreased in RA patients with highly significant differences as compared with healthy control. Highly significant serum levels of oxidative DNA damage in RA patients were observed compared to the control group. Body Mass Index (BMI) results indicted significant differences between RA patients and healthy control. It can, therefore, be concluded that there is a potential role if malondialdehyde, oxidative DNA damage and GPX3 are used as biomarkers for progression of in patients with RA.